Assessing the impact of Self Esteem & Optimism on Subjective Well-Being: A moderation model - Abhishek Singhal Dr. Priyanka Nema , Dr. Bhanu Priya (International Journal of Advanced Science and Technology, 2020)
The study aims to show impact of Self-esteem, Mastery and Optimism on Subjective Well-being (SWB). Standard measures for Self-esteem, Mastery and Optimism are being used. The results showed a clear significant and positive correlation of Self Esteem, Mastery and Optimism on Subjective Well-being. A step-wise regression model is created to examine the impact of all the independent factors (Self-esteem, Mastery and Optimism) on dependent factor (Subjective well-being). Finally, optimism as a moderator between relationship of self-esteem and SWB is examined. The result shows that optimism indeed moderates the impact of self-esteem on SWB. Results are discussed in the end of the study with implications and future directions of the study.